Prevalence of human papillomavirus infection in oocyte donors and women treated for infertility: An observational laboratory-based study - Hana Jaworek; Blazena Zborilova; Vladimira Koudelakova; Jana Brezinova; Jana Vrbkova; Ivana Oborna; Marian Hajduch (Elsevier, 2019)
Objective: The aims of this study were to determine the prevalence of human papillomavirus (HPV) infection in women treated for infertility and oocyte donors, and to investigate the possible influence of HPV infection on reproductive outcomes. Study design: In this observational laboratory-based study, cervical swabs were collected from oocyte donors (n = 207), and women treated for infertility (n = 945) and analysed for the presence of high-risk HPV (hrHPV) genotypes using the cobas® 4800 HPV Test and PapilloCheck® HPV-Screening. Associations between hrHPV positive status and fertility outcome or socio-behavioral and health characteristics were evaluated using R statistical software. Results: HrHPV prevalence was significantly higher in oocyte donors than in women treated for infertility (28.0% vs. 16.1%, P <  0.001). Women who became pregnant spontaneously (19.6%) and women not treated with in vitro fertilization (IVF, 18.1%) were more frequently hrHPV positive than women treated with IVF (12.7%, P = 0.077). Despite the high prevalence of hrHPV in both oocyte donors and infertile women, no associations between hrHPV positive status and pregnancy or abortion rates were found in IVF treated women or in oocyte recipients. Moreover, no associations between hrHPV positive status and abortion rates were found in spontaneously pregnant women. Conclusion: Despite the high prevalence of hrHPV in both oocyte donors and infertile women, HPV infection did not influence the outcomes of assisted reproductive technology. Keywords: Human papillomavirus, Infertility, In vitro fertilization, Pregnancy, Oocyte donor